Evaluation and costs of different haemoglobin methods for use in district hospitals in Malawi. Issue 1 (27th December 2004) - Medina Lara, A; Mundy, C; Kandulu, J; Chisuwo, L; Bates, I
Abstract : Aims: To evaluate the characteristics of manual haemoglobin methods in use in Malawi and provide evidence for the Ministry of Health in Malawi to enable them to choose a suitable method for district hospitals. Methods: Criteria on accuracy, clinical usefulness, user friendliness, speed, training time, and economic costs were determined by local health professionals and used to compare six different manual haemoglobin methods. These were introduced sequentially into use in a district hospital in Malawi alongside the reference method. Results: HemoCue was the optimal method based on most of the outcome measures but was also the most expensive (US$0.75/test). DHT meter and Jenway colorimeter were the second choice because they were cheaper (US$0.20–0.35/test), but they were not as accurate or user friendly as HemoCue. Conclusions: The process for choosing appropriate laboratory methods is complex and very little guidance is available for health managers in poorer countries. This paper describes the development and testing of a practical model for gathering evidence about test efficiency that could be adapted for use in other resource poor settings.